How war came tot America : from the fall of France to Pearl Harbour - Davis, Forrest; Lindley, Ernest Kidder (London : George Allen & Unwin, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; internationale relaties; Verenigde Staten